Sosialisasi Petugas Rekam Medis Terhadap Penggunaan Sistem Informasi Registrasi Di Puskesmas Tumbuan - Ismail Arifin; Nofri; VICKY ANANDA HARAHAP; LEZZA AFRILIA UTARI (Abdi Reksa, 2023)
The information system is a combination of people, facilities, technology that aims to obtain important communication lines for both internal and external needs. Tumbuan Health Center is one of the health facilities that recently implemented a registration information system for its patients. The existing puskesmas information system (simpus) has just been created and has not yet been implemented for existing officers. In this service activity, there will be socialization of understanding to medical record officers on the use of registration information systems. This was done because previously at the Tumbuan Health Center, they still registered manually, in order to minimize errors in using the system. Then socialization will be given to 4 medical record officers regarding the use of the new system. The method used in this case is to provide pre and post tests to the medical record officer. by giving pre and post tests can find out the understanding of officers before and after being given socialization. Known after being given socialization officers understand and understand how to use the patient registration information systm. Officers find it easy to register, Report printing only takes <10 minutes, Officers are satisfied with the patient registration system at the Tumbuan health center